2018
DOI: 10.1016/j.celrep.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

CAST/ELKS Proteins Control Voltage-Gated Ca2+ Channel Density and Synaptic Release Probability at a Mammalian Central Synapse

Abstract: In the presynaptic terminal, the magnitude and location of Ca entry through voltage-gated Ca channels (VGCCs) regulate the efficacy of neurotransmitter release. However, how presynaptic active zone proteins control mammalian VGCC levels and organization is unclear. To address this, we deleted the CAST/ELKS protein family at the calyx of Held, a Ca2.1 channel-exclusive presynaptic terminal. We found that loss of CAST/ELKS reduces the Ca2.1 current density with concomitant reductions in Ca2.1 channel numbers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(113 citation statements)
references
References 61 publications
(111 reference statements)
6
104
1
Order By: Relevance
“…Here, we first expected that neglect in CAST KO dams might be caused by impaired OXT release. Indeed, previous studies indicated an essential role for CAST in recruiting Ca 2+ channels that can trigger neurotransmitter release at the active zone 21,22,25,[41][42][43] , as well as the OXT release depends on Ca 2+ influx into the axon terminal 44,45 . Our findings showed that magnocellular neuron terminals in the posterior pituitary were intensely labelled for CAST and OXT (Fig.…”
Section: Scientific Reports |mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we first expected that neglect in CAST KO dams might be caused by impaired OXT release. Indeed, previous studies indicated an essential role for CAST in recruiting Ca 2+ channels that can trigger neurotransmitter release at the active zone 21,22,25,[41][42][43] , as well as the OXT release depends on Ca 2+ influx into the axon terminal 44,45 . Our findings showed that magnocellular neuron terminals in the posterior pituitary were intensely labelled for CAST and OXT (Fig.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Previous work has shown that mutant forms of CAST/ELKS homologs in C. elegans (ELKS) and Drosophila (bruchpilot) exhibit distinct phenotypes, indicating they are required for synapse formation in C. elegans and for the promotion of active zone assembly in Drosophila 19,20 . Furthermore, analysis of CAST and/or ELKS deficient mice indicated that these proteins affect calcium channel-associated release machinery in retinal photoreceptor neurons, hippocampal neurons, calyx of the Held/MNTB synapses, and pancreatic β cells [21][22][23][24][25][26] . However, despite the importance of presynaptic events, only a few studies have reported the contribution of presynaptic neurotransmitter release to maternal behaviour 2,27 .…”
mentioning
confidence: 99%
“…Genetic studies of mammalian retinal ribbon synapses in vivo which deleted both CAST/ELKS identified roles for CAST/ELKS regulation of synapse formation and AZ morphology (Hagiwara et al 2018). However, deletion of both CAST/ELKS at the mature calyx of Held in vivo, a large Ca V 2.1 exclusive glutamatergic presynapse with many conventional AZs in parallel (Baydyuk et al 2016), led to no changes in presynaptic morphology or AZ ultrastructure (Dong et al 2018). In addition, studies on in vitro cultured hippocampal neurons deleted for both CAST/ELKS found no changes in AZ ultrastructure in GABAergic neurons (Liu et al 2014) or in glutamatergic neurons (Held et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is unclear if the roles of CAST/ELKS in regulating synapse development and AZ ultrastructure are unique to ribbon synapses, or whether these roles are confined to a specific developmental stage of synapse maturation. In addition, although a role for CAST/ELKS was found for regulating Ca V 2.1 current levels and channel numbers in a Ca V 2.1 exclusive presynaptic terminal (Dong et al 2018), it is not known if CAST/ELKS regulate all presynaptic Ca V 2 subtype levels or if they are solely Ca V 2.1-specific.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation